DETECTION OF BLANDM-1 GENE IN PROVIDENCIA RETTGERI ISOLATED FROM DIABETIC FOOT ULCERS OF FOUR PATIENTS FROM INDIA - SAMANT SA,; MARATHE N,; VAISHAMPAYAN A, (International Journal of Pharma and Bio Sciences, 2015)
Providencia rettgeri is associated with various infections, including skin infections, diarrhea, bacteremia and urinary tract infections (UTI) andmany hospital acquired infections. Carbapenems are mainstay of treatment fordrug resistant bacterial infections. Enzyme New Delhi Metallo β Lactamase-1encoded by the gene blaNDM-1 make these bacteria resistant to carbapenems. This gene is located ontransmissible plasmid which may include other antibiotic resistance genes.A total of four strains of Providencia rettgeriwas isolated from the wound swabs ofpatients with diabetic foot ulcer. They were screened for the production of carbapenemase and confirmed byPolymerase Chain Reaction amplification and sequencing the blaNDM-1 gene. Presence of this gene can be a potential risk factor in management of diabetic foot infections, which can lead to systemic toxicity and setting of gangrene. To our knowledge this is the first report ofProvidencia rettgeri with blaNDM-1 isolated from diabetic patients in India.